Keakuratan Metode Bioassay dalam Mendeteksi Herbisida Pratumbuh Ametrin dan Diuron dalam Tanah dan Air - Nanik Sriyani (Jurnal Agrista, 2008)
Accuracy of Bioassay Technique for Detection of Preemergence Herbicides Ametryn and Diuron in Soil and WaterABSTRACT. The objective of this study is to know the accuracy of the bioassay technique developed to detect ametryn and diuron herbicides in soil and water. Ametryn and diuron are two of several premergence herbicides currently used extensively in Indonesia expecially in plantations crops. The extensive used of the herbicides raised concern about their residue in soil and water and its negative effects. This study is a second step of three steps of experiments aimed to develop a method to detect the amount of herbicides in soil and water using a simple, easy, and economical using bioassay technique. In the previous first step, indicators plant and standard curves for ametryn and diuron were already determined. The objective of this study is to know the accuracy of the bioassay technique to detect ametryn and diuron herbicides in soil and water. Test curve were developed to evaluate accuracy between the amount of herbicide applied compared with the amount calculate of bioassay methods. Test curve is a linier correlation between amount of herbicide applied and the amount detected by bioassay method, stated as Y = a + bX, Y is the amount calculate by bioassay and X is the amount applied. If the amount calculate by bioassay is the same as the amount applied, the test cuve become Y = X, so a must be equal to 0 and b equal to 1 (a=0 and b=1), which means the bioassay method is accurate. Result showed that bioassay could be used to detect ametryn accurately in soil using caisim as indicator-plant, by measuring its shoot length or shoot dry weight. However, this indicator plant could not detect ametryn in water accurately. Bioassay could also be used to detect diuuron accurately both in soil and in water using cucumber as indicator-plant, by measuring its shoot or root length, as well as shoot or root dry weight.